Allergic reactions to local anesthetics: should we test those with drug allergies and atopy history? - Yildiz, Eray; Colkesen, Fatih; Sadi Aykan, Filiz; Evcen, Recep; Kilinc, Mehmet; Aytekin, Gokhan; Arslan, Sevket (Annals of Medical Research, 2022)
Aim: Many patients are referred to allergy clinics for allergy tests to local anesthetics. The aim of this study was to evaluate the effect of a history of atopy and drug hypersensitivity on allergy tests made with local anesthetics.Materials and Methods: A retrospective review was made of the records of patients referred to our clinic within a 5-year period because of a suspicion of allergy to local anesthetics, and who were applied with skin tests and subcutaneous challenge tests.Results: Evaluation was made of a total of 138 patients, comprising 114 (82.6%) females and 24 (17.4%) males with a mean age of 45.35 ± 14.13 years. A reaction during a dental procedure was reported in 99 (71.7%) patients. Mepivacaine was the most tested local anesthetic (n = 66, 40.2%).  A positive reaction was determined in the skin tests made with local anesthetics in 6 (4.3%) patients. Lidocaine was the local anesthetic most often showing a positive reaction (n = 3, 50%). A history of atopy was present in 30 (21.7%) patients. No correlation was determined between atopy history and the development of a positive reaction to local anesthetics (p = 0.086). In the cases determined with a positive reaction to local anesthetics, there was a greater rate of history of hypersensitivity to drugs other than local anesthetics (p = 0.012).Conclusion: Patients with a history of drug hypersensitivity reaction should be tested in respect of local anesthetic allergy prior to a procedure to be made with local anesthetics.
Keywords: Local anesthetics; allergy; drug hypersensitivity; anaphylaxis; skin tests